First Report of Apinisia keratinophila Isolated from Soil in Korea - Song-Woon Nam; Leonid N. Ten; Seong-Keun Lim; Soo-Min Hong; Seung-Yeol Lee; HeeYoung Jung (한국균학회지)
In 2022, a fungal isolate, designated KNUF-22-049, was obtained from a soil sample collected from a field in Sang-ju, Gyeongsangbuk-do, Korea. The strain exhibited cultural and morphological characteristics, including colony color and size and the shapes and sizes of conidiogenous cells and conidia, that were consistent with those of Apinisia keratinophila. A phylogenetic analysis using the sequences of the internal transcribed spacer regions and the large subunit of the nuclear ribosomal RNA gene confirmed that isolate KNUF-22-049 is most closely related to A. keratinophila CBS 947.73T at a species level. Both the morphological observations and phylogenetic analysis indicated that KNUF-22-049 is indeed an A. keratinophila strain. This study represents the first documentation of Apinisia keratinophila in Korea.